Transitions at the top : - Ciampa, Dan (Wiley, 2015)
Many books have been written for new CEOs on what they need to do when they take charge at a new company, but few focus on what the rest of the organization has to do to set up the new leader--and the rest of the organization--for success. During any transition of C-suite leadership, the board of directors, the outgoing CEO (if there is one), the Chief Human Resources Officer, and other influential senior executives all play a crucial role in achieving a successful transition. What does it take to focus the organization, culture, systems, and processes so that the entire company lays a foundation for success?Transitions at the Top tells companies everything they need to know to successfully maintain continuity as one leader passes the mantle of responsibility to a successor, spanning the steps &​ events from the point that a candidate for a top position accepts the offer, all the way through to the point that a critical mass of followers accepts him/​her as the established leader. The book includes advice for each role who will be managing the transition